Evaluasi Pengalaman Pengguna Spotify dan YouTube Music Menggunakan Metode User Experience Questionnaire - Stefanus Francois Saro Harefa; Christ Rudianto (STMIK Banjarbaru, 2025)
Despite the popularity of Spotify and YouTube Music in Indonesia, reviews from the Google Play Store show several complaints regarding bugs and errors in the application's features and functions that affect the user experience. Using the User Experience Questionnaire (UEQ) method, this research aims to evaluate and compare the user experience of the two applications through a quantitative approach from a scale of attractiveness, clarity, efficiency, reliability, stimulation and novelty. 253 valid respondent data shows that both applications received positive ratings on all UEQ scales. However, benchmark results show that Spotify gets good scores on five scales, while YouTube Music only scores on one scale. The T-test results show significant differences between the two applications on the 5 UEQ scales, except on the reliability scale. Overall, this research provides insight into user experience and confirms the importance of continuous development of UX aspects for application developers in improving user experience.Keywords: Spotify; YouTube Music; User Experience Questionnaire; User experience AbstrakTerlepas dari kepopuleran Spotify dan YouTube Music di Indonesia, ulasan dari Google Play Store menunjukkan beberapa keluhan terkait bug dan error pada fitur serta fungsionalitas aplikasi yang memengaruhi pengalaman pengguna. Dengan metode User Experience Questionnaire (UEQ), penelitian ini bertujuan untuk mengevaluasi dan membandingkan pengalaman pengguna kedua aplikasi melalui pendekatan kuantitatif dari skala daya tarik, kejelasan, efisiensi, keandalan, stimulasi, dan kebaruan. 253 data responden yang valid menunjukkan kedua aplikasi mendapatkan evaluasi positif pada seluruh skala UEQ. Namun, Hasil benchmark menunjukkan Spotify dinilai excellent pada lima skala, sementara YouTube Music hanya pada satu skala. Hasil uji T-test menunjukkan perbedaan signifikan antara kedua aplikasi pada 5 skala UEQ, kecuali skala keandalan. Secara keseluruhan, penelitian ini memberikan wawasan terkait pengalaman pengguna dan menegaskan pentingnya pengembangan berkelanjutan pada aspek UX bagi pengembang aplikasi dalam meningkatkan pengalaman pengguna.Kata kunci: Spotify; YouTube Music; User Experience Questionnaire; Pengalaman pengguna